Learning Health Equity Frameworks within a Community of Scholars - Alexander, Kamila A. (2011)
Scholars in nursing science have long espoused the concept of health equity without specifically using the term or dialoguing about the social determinants of health and social justice. In this paper, we describe the development, implementation, and evaluation of a doctoral and post- doctoral seminar collective entitled Health Equity: Conceptual, Linguistic, Methodological and Ethical Issues. The course enabled scholars-in-training to consider the construct and its nuances and frame a personal philosophy of health equity. We offer an example of how a group of emerging scholars can engage in the important, but difficult discourse related to health equity. The collective provided a forum for debate, intellectual growth, and increased insight for students and faculty. We posit that the lessons learned by all participants have the potential to enrich doctoral and post-doctoral scientific training in nursing science and may serve as a model for other research training programs in the health sciences.